Comparative Trace Elemental Analysis in Cancerous and Noncancerous Human Tissues Using PIXE - Mulware, Stephen Juma (Hindawi Publishing Corporation, 2013)
The effect of high or low levels of trace metals in human tissues has been studied widely. There have been detectable significant variations in the concentrations of trace metals in normal and cancerous tissues suggesting that these variations could be a causative factor to various cancers. Even though essential trace metals play an important role such as stabilizers, enzyme cofactors, elements of structure, and essential elements for normal hormonal functions, their imbalanced toxic effects contribute to the rate of the reactive oxygen species (ROS) and formation of complexities in the body cells which may lead to DNA damage. The induction of oxidative-induced DNA damage by ROS may lead to isolated base lesions or single-strand breaks, complex lesions like double-strand breaks, and some oxidative generated clustered DNA lesions (OCDLs) which are linked to cell apoptosis and mutagenesis. The difference in published works on the level of variations of trace metals in different cancer tissues can be attributed to the accuracy of the analytical techniques, sample preparation methods, and inability of taking uniform samples from the affected tissues. This paper reviews comparative trace elemental concentrations of cancerous and noncancerous tissues using PIXE that has been reported in the published literature.